Macrophage NCOR1 protects from atherosclerosis by repressing a pro-atherogenic PPARγ signature. (16th September 2019) - Oppi, Sara; Nusser-Stein, Stefanie; Blyszczuk, Przemyslaw; Wang, Xu; Jomard, Anne; Marzolla, Vincenzo; Yang, Kangmin; Velagapudi, Srividya; Ward, Liam J; Yuan, Xi-Ming; Geiger, Martin A; Guillaumon, Ana T; et al.
Abstract: Aims: Nuclear receptors and their cofactors regulate key pathophysiological processes in atherosclerosis development. The transcriptional activity of these nuclear receptors is controlled by the nuclear receptor corepressors (NCOR), scaffolding proteins that form the basis of large corepressor complexes. Studies with primary macrophages demonstrated that the deletion of Ncor1 increases the expression of atherosclerotic molecules. However, the role of nuclear receptor corepressors in atherogenesis is unknown. Methods and results: We generated myeloid cell-specific Ncor1 knockout mice and crossbred them with low-density lipoprotein receptor ( Ldlr ) knockouts to study the role of macrophage NCOR1 in atherosclerosis. We demonstrate that myeloid cell-specific deletion of nuclear receptor corepressor 1 (NCOR1) aggravates atherosclerosis development in mice. Macrophage Ncor1 -deficiency leads to increased foam cell formation, enhanced expression of pro-inflammatory cytokines, and atherosclerotic lesions characterized by larger necrotic cores and thinner fibrous caps. The immunometabolic effects of NCOR1 are mediated via suppression of peroxisome proliferator-activated receptor gamma (PPARγ) target genes in mouse and human macrophages, which lead to an enhanced expression of the CD36 scavenger receptor and subsequent increase in oxidized low-density lipoprotein uptake in the absence of NCOR1. Interestingly, in human atherosclerotic plaques, the expression of NCOR1 is reduced whereas the PPARγ signature is increased, and this signature is more pronounced in ruptured compared with non-ruptured carotid plaques. Conclusions: Our findings show that macrophage NCOR1 blocks the pro-atherogenic functions of PPARγ in atherosclerosis and suggest that stabilizing the NCOR1–PPARγ binding could be a promising strategy to block the pro-atherogenic functions of plaque macrophages and lesion progression in atherosclerotic patients.